Impact of frailty on adverse outcomes in patients with abdominal aortic aneurysm undergoing surgery: a systematic review and meta-analysis - Junfang Zhang; Yue Qiu; Heng Zhang; Yu Fan (Elsevier, 2024)
Objective: To explore the prognostic role of frailty in patients with abdominal aortic aneurysm (AAA) by conducting this systematic review and meta-analysis Methods: We conducted an extensive literature search on PubMed, Web of Sciences, and Embase databases to identify studies that reported the association of frailty with postoperative complications, reintervention, or all-cause mortality in patients with AAA after surgery. Short-term mortality was defined by a combination of in-hospital and 30-day death. Results: Seven cohort studies reporting on 9 articles with 323,788 AAA patients were included. The reported prevalence of frailty in AAA patients ranged between 2.3% and 34.6%. Pooling the results revealed that frailty was significantly associated with a higher risk of short-term all-cause mortality (adjusted risk ratios [RR] 3.20; 95% confidence intervals [CI] 1.95-5.26), long-term all-cause mortality (adjusted RR 2.86; 95% CI 2.57-3.17), and postoperative complications (adjusted RR 2.19; 95% CI 1.50-3.20) compared to non-frail individuals. However, there was no clear association between frailty and reintervention (HR 1.44; 95% CI 0.97-2.16). Conclusions: Frailty independently predicts the short and long-term survival as well as postoperative complications in patients with AAA undergoing surgery. Assessing frail status may potentially enhance surgical decision-making for these patients.